Assessment of goitre among primary school children in district Chamba, Himachal Pradesh, India - Dhiman, Arvind Kumar; Sandhu, Sumita Kumari; Yadav, Vijay Kumar; Arora, Ishan (International Journal Of Community Medicine And Public Health, 2020)
Background: Goiter is one of the most visible manifestations of iodine deficiency disorders (IDD) that is caused due to overstimulation of thyroid as an adaptation to Iodine deficiency. IDD is among the major public health threats and important micronutrient deficiencies in developing countries. Methods: This cross-sectional study was conducted among 6-12 years school children in district Chamba of Himachal Pradesh from February to June 2019. The sample size of 336 was calculated and a total of 504 children from government schools were enrolled in the study. The assessment of goitre was done clinically by inspection and palpation of thyroid gland. Results: In this study, 504 school aged children of 6-12 yrs from district Chamba with mean age of 9±1.86 years were included. The prevalence of total goitre rate was 16% with mean age of 8.75±1.37 years. The highest prevalence (%) was observed in age of 10 years (28.4%) followed by 8 years and 9 years (25.9 % and 23.5% respectively). Conclusions: This study showed mild goitre prevalence in school aged children of 6-12 years in district Chamba of Himachal Pradesh. There is dire need of periodic survey to assess the magnitude of IDD in future.